2022
DOI: 10.3390/biomedicines10061368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Inflammatory and Neurotrophic Biomarkers in Bipolar Disorder: A Systematic Review and Meta-Analysis

Abstract: Bipolar disorder (BD) is a multifactorial chronic psychiatric disease highly defined by genetic, clinical, environmental and social risk factors. The present systematic review and meta-analysis aimed to examine the relationship between inflammatory and neurotrophic factors and clinical, social and environmental factors involved in the development and the characterization of BD. Web of Science, PubMed, PsycINFO, Scopus and Science Direct were searched by two independent reviewers. The systematic review was regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…New treatments for BD are being studied, and most target disparate effector systems, mainly related to molecular targets in neuroplasticity, neurotrophic factors, inflammation, stress, mitochondrial function, and related metabolic pathways [46][47][48]. Clinical trials have demonstrated the efficacy of adjunctive inflammatory modulation with celecoxib in treatment-resistant bipolar depression, showing that add-on celecoxib reduces treatment resistance and enhances antidepressant response in patients with treatment-resistant bipolar depression [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…New treatments for BD are being studied, and most target disparate effector systems, mainly related to molecular targets in neuroplasticity, neurotrophic factors, inflammation, stress, mitochondrial function, and related metabolic pathways [46][47][48]. Clinical trials have demonstrated the efficacy of adjunctive inflammatory modulation with celecoxib in treatment-resistant bipolar depression, showing that add-on celecoxib reduces treatment resistance and enhances antidepressant response in patients with treatment-resistant bipolar depression [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…BDNF is a well-established antiinflammatory mediator (201), involved in neurogenesis and with neurotrophic effects (202), whose blood and brain levels decrease with peripheral inflammation. Several works indicate that BDNF may play a role in BD pathogenesis and neuroplasticity changes associated with the disorder (203,204). ELS, such as trauma, has also been shown to increase the risk for BD (205)(206)(207) and lead to unfavourable symptoms and disease progression (208).…”
Section: Inflammatory Markers Sleep and Gut Health: The Effects Of In...mentioning
confidence: 99%
“…In particular, due to its consistent alterations in BD patients, IL-6 has recently been proposed as a potential BD marker (218). However, some of these associations are not encountered or presented in the opposite direction in other works (203,218).…”
Section: Inflammatory Markers Sleep and Gut Health: The Effects Of In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the underlying pathophysiology of RESLES is not yet well understood, studies have indicated that it is related to inflammation, intramyelinic cytotoxic edema ( 8 ), oxidative stress ( 9 ), and autoimmune processes ( 10 ). Vega-Nunez et al ( 11 ) mentioned in their review that there is a certain association between inflammatory biomarkers and mood episode, such as tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP), cytokines, etc. Serum levels of these inflammatory biomarkers may increase or decrease with different mood episode.…”
Section: Introductionmentioning
confidence: 99%